Intersections of Gender, Class, and Race in the Long Nineteenth Century and Beyond
XVI, 328 p. 1 illus.
Keywords: This book explores the intersections of gender with class and race in the construction of national and imperial ideologies and their fluid transformation from the Romantic to the Victorian period and beyond, exposing how these cultural constructions are deeply entangled with the family metaphor. For example, by examining the re-signification of the “angel in the house” and the deviant woman in the context of unstable or contingent masculinities and across discourses of class and nation, the volume contributes to a more nuanced understanding of British cultural constructions in the long nineteenth century. The central idea is to unearth the historical roots of the family metaphor in the construction of national and imperial ideologies, and to uncover the interests served by its specific discursive formation. The book explores both male and female stereotypes, enabling a more perceptive comparison, enriched with a nuanced reflection on the construction and social function of class. .